Gut microbiota dysbiosis with hepatitis B virus liver disease and association with immune response - Yan, Fengna; Zhang, Qun; Shi, Ke; Zhang, Yi; Zhu, Bingbing; Bi, Yufei; Wang, Xianbo (Frontiers in Cellular and Infection Microbiology, 2023)
Background and aims Given hepatitis B virus (HBV)-related hepatocellular carcinoma (HBV-HCC) exhibits unique gut microbiota characteristics and a significant immunosuppressive tumor microenvironment. Thus, a better understanding of the correlation between gut microbiota and the immunosuppressive response may help predict occurrence and prognosis of HBV-HCC. Methods Here, in a cohort of ninety adults (healthy control n=30, HBV-cirrhosis n=30, HBV-HCC n=30) with clinical data, fecal 16S rRNA gene sequencing, matched peripheral blood immune response with flow cytometry analysis. Correlation between the gut microbiome of significantly different in HBV-HCC patients and clinical parameters as well as the peripheral immune response was assessed. Results We found that community structures and diversity of the gut microbiota in HBV-CLD patients become more unbalanced. Differential microbiota analysis that p:Acidobacteriota, p:Proteobacteria, p:Campilobacterota, f:Streptococcaceae, g:Klebsiella associated with inflammation were enriched. The beneficial bacteria of f:Clostridia UCG−014, f:Oscillospiraceae, f:_Rikenellaceae, g:_Barnesiella, g:Prevotella, g:Agathobacter were decreased. Functional analysis of gut microbiota revealed that lipopolysaccharide biosynthesis, lipid metabolism, butanoate metabolism were significantly elevated in HBV-CLD patients. Spearman’s correlation analysis showed that Muribaculaceae, Akkermaniacaeae, [Eubacterium]_coprostanoligenes_group, RF39, Tannerellaceae have positive correlation with CD3+T, CD4+T and CD8+T cell counts while negatively correlated with liver dysfunction. Furthermore, paired peripheral blood showed a decreased proportion of CD3+T, CD4+T and CD8+T cells, while an increased T (Treg) cells. The immunosuppressive response of programmed cell death 1 (PD-1), cytotoxic T-lymphocyte antigen 4 (CTLA-4), immune receptor tyrosine based inhibitor motor (ITIM) domain (TIGIT), T-cell immune domain, and multiple domain 3 (TIM-3) of CD8+T cells were higher in HBV-HCC patients. They were positively correlated with harmful bacteria, such as Actinobaciota, Myxococota, Streptococcaceae and Eubacterium coprostanoligenes. Conclusions Our study indicated that gut beneficial bacteria, mainly Firmicutes and Bacteroides appeared dysbiosis in HBV-CLD patients. They have negative regulation of liver dysfunction and T cell immune response. It provides potential avenues for microbiome-based prevention and intervention for anti-tumor immune effects of HBV-CLD.